Review on non-thermal plasma technology: FROM aflatoxins degradation to effect on medicinal plants - Kimia Taki; Bahram Hosseinzadeh Samani (Future Natural Products)
Background and aims: Aflatoxins, toxic secondary metabolites produced by certain fungi, pose significant risks to human and animal health due to their presence in food and agricultural products. Traditional methods of aflatoxin degradation often compromise product quality. This study aimed to evaluate the effectiveness of cold plasma technology in degrading aflatoxins while preserving the quality of the treated products. Methods: A comprehensive review of the current literature focused on studies that applied cold plasma technology for aflatoxin degradation. The analysis included parameters such as plasma generation methods, exposure times, and the impact on the nutritional and sensory quality of the treated products. Results: Cold plasma technology significantly degraded aflatoxins across different food matrices. Its low-temperature operation ensures minimal impact on the quality of agricultural and food products, making it especially suitable for temperature-sensitive items. The technology works by generating reactive species that target and neutralize the toxic properties of aflatoxins. Conclusion: Compared to traditional methods, cold plasma offers a safer and more efficient alternative for aflatoxin degradation. Cold plasma technology presents a promising solution for aflatoxin degradation with significant advantages over conventional methods. Its ability to maintain product quality while effectively neutralizing aflatoxins underscores its potential for broader application in food safety management. Further research is warranted to optimize its use and fully understand its implications for human and animal health.